TEM technique in the treatment of patients with early rectal cancer - P. N. Romaschenko; A. A. Sazonov; N. A. Maistrenko; D. A. Ilyasbekov (Вестник хирургии имени И.И. Грекова, 2020)
The use of organ-preserving interventions remains the most important direction in improving of surgical treatment of patients with rectal cancer. One of the promising options for its implementation is the TEM (transanal endoscopic microsurgery) technique, which allows local removal of rectal neoplasms by its full-wall resection. However, indications for this intervention are still a matter of debate. The presented clinical case demonstrates the positive potential of the TEM technique, which consists of reducing surgical trauma without violating the basic oncological principles.